Evaluation of Properties and Mechanisms of Waste Plastic/Rubber-Modified Asphalt - Xiaorui Zhang (MDPI AG, 2021)
Waste plastic, such as polyethylene (PE), and waste rubber tires, are pollutants that adversely affect the environment. Thus, the ways these materials are used are important in realizing the goals of reduced CO2 emissions and carbon neutrality. This paper investigates the fundamental properties, compatibility, and interaction mechanism of waste plastic/rubber-modified asphalt (WPRMA). Dynamic shear rheology, fluorescence microscopy, a differential scanning calorimeter, and molecular dynamic simulation software were used to evaluate the properties and mechanisms of WPRMA. The results show that the anti-rutting temperature of WPRMA with different waste plastic contents is higher than 60 °C and the optimal dosage of waste PE in WPRMA is 8%, which can enhance the high-temperature properties and compatibility of rubber-modified asphalt. The temperature can directly promote the melting and decomposition of the functional groups in WPRMA and thus must be strictly controlled during the mix production process. The interaction mechanism suggests that waste plastic can form networks and package the rubber particles in rubber-modified asphalt. The main force between waste plastic and rubber is Van der Waals force, which rarely occurs in chemical reactions.